2015
DOI: 10.17660/ejhs.2015/80.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant compounds and activity in cucumber fruit in response to foliar and soil humic acid application

Abstract: What is already known on this subject?• Humic acid with its hormon-like activity improves the yield and quality of fruits and vegetables. Cucumber fruit has a very low level of antioxidants, and it is not known if humic acid can improve the antioxidant content of cucumber fruit.What are the new findings?• The application of humic acid improves cucumber fruit quality by enhancing its content of antioxidant compounds.What is the expected impact on horticulture?• Cucumber fruit with high contents of antioxidant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Nevertheless, the authors found out that foliar treatments might be the best use-case for improving cucumber fruit quality, as a 10 mL L −1 foliar regimen yielded the highest increments of total soluble sugars (+14.4%) and reducing sugars (+25.3%). In a later study by the same authors, a further increase to 20 mL L −1 foliar applications recorded the highest increases in fruit antioxidant activity, either lipophilic (+31.7%) and hydrophilic (+148%), total carotenoids (+74.2%), lycopene (+120.8%), and β-carotene (+92.8%) contents compared to the untreated controls [138].…”
Section: Cucurbit Fruit Quality Modulation After Biostimulant Applicationsmentioning
confidence: 78%
“…Nevertheless, the authors found out that foliar treatments might be the best use-case for improving cucumber fruit quality, as a 10 mL L −1 foliar regimen yielded the highest increments of total soluble sugars (+14.4%) and reducing sugars (+25.3%). In a later study by the same authors, a further increase to 20 mL L −1 foliar applications recorded the highest increases in fruit antioxidant activity, either lipophilic (+31.7%) and hydrophilic (+148%), total carotenoids (+74.2%), lycopene (+120.8%), and β-carotene (+92.8%) contents compared to the untreated controls [138].…”
Section: Cucurbit Fruit Quality Modulation After Biostimulant Applicationsmentioning
confidence: 78%
“…Aminifard et al (2012) reported that HA application (250 mg kg -1 ) treatment significantly improved the antioxidant activity, total flavonoid, capsaicin, lycopene, and β-carotene in the fruits of hot pepper under field conditions. In another study with cucumber plants grown under field conditions, Karakurt et al (2015) found that the foliar as well as soil application of HA improved the fruit quality of cucumber and they attributed this improvement to HA-induced antioxidant potential particularly xanthophyll, total phenolics and β-carotene.…”
Section: Discussionmentioning
confidence: 99%
“…The highest POD activity was observed in the 6 g HA kg −1 soil, and the highest CAT activity was observed in the 3 g HA kg −1 soil. Many researchers have also reported that the application of HA was effective in improving stress tolerance by increased activity of POD and CAT in eggplant ( Solanum melongena L.) (Kiran et al, 2014), date plam ( Phoenix dactylifera L.) (Balaket, 2014), hot pepper (Aminifard et al, 2012), and cucumber (Karakurt et al, 2015). In contrast to our results, Kaya et al (2018) found that exogenously applied HA reduced the activity of the POD and CAT enzymes under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%